1973
DOI: 10.1099/00207713-23-4-333
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic Acid Homologies in the Genus Pseudomonas

Abstract: On the basis of ribosomal ribonucleic acid homologies, the genus Pseudomonas can be divided into at least five distinct groups, some of which are as distantly related t o each other as they are to Escherichia coli. One of these groups contains members of the genus Xanthomonas. The data presented support and extend the previous grouping based on deoxyribonucleic acid homologies and support the current view that the portion of the genome coding for ribosomal ribonucleic acid is more conserved in the course of ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

24
261
2
12

Year Published

1989
1989
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 503 publications
(299 citation statements)
references
References 7 publications
24
261
2
12
Order By: Relevance
“…In our first paper on Pseudomonas (14), we confirmed in this genus sensu Doudoroff and Palleroni (20) five different rRNA branches. These branches correspond extremely well with the Palleroni rRNA homology groups (41,43), although the latter were derived from a very small number of strains. However, we proved that these groups are genotypically too far removed from each other to be united in a single genus; furthermore, we established their exact relationship with other gram-negative genera (14).…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…In our first paper on Pseudomonas (14), we confirmed in this genus sensu Doudoroff and Palleroni (20) five different rRNA branches. These branches correspond extremely well with the Palleroni rRNA homology groups (41,43), although the latter were derived from a very small number of strains. However, we proved that these groups are genotypically too far removed from each other to be united in a single genus; furthermore, we established their exact relationship with other gram-negative genera (14).…”
mentioning
confidence: 75%
“…In the past and even today organisms isolated from a heterogeneous variety of ecological niches were and still are classified without sufficient grounds as new Pseudomonas species. One of the reasons for this situation is the incomplete generic definition.In the United States, the Berkeley group has reported in several papers (42,43,48) on the taxonomy of the genus Pseudomonas. The several hundred strains included in the important study of these workers involved only a relatively small number of species.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because atypical strains of fluorescent Pseudomonas spp. in ribosomal Ribonucleic Acid (rRNA) similarity group 1 [43] can occasionally be confused using FAME analysis [42], identifications of these isolates were verified by growth at high (42) and low (3C) temperatures and by their ability to hydrolyse gelatin [25].…”
Section: Microbial Identificationmentioning
confidence: 99%
“…Because of its economic importance, this genus has been subjected to many taxonomic and determinative studies. DNA-rRNA hybridizations (4, 17) have revealed that the genus constitutes a separate rRNA branch in the gamma taxon of the Proteobacteria (sensu Stackebrandt et al [21]). In Bergey's Manual of Systematic Bacteriology, the genus is divided into the following five species (1): Xanthomonas albilineans, Xanthomonas ampelina, Xanthomonas axonopodis, Xanthomonas campestris (type species), and Xanthomonas fragariae.…”
mentioning
confidence: 99%